2009
DOI: 10.1203/pdr.0b013e31818d6850
|View full text |Cite
|
Sign up to set email alerts
|

Severe Intrauterine Growth Restriction Is Associated With Higher Spontaneous Carbohydrate Intake in Young Women

Abstract: Intrauterine growth restriction (IUGR) is associated with metabolic disorders in adulthood. In rats, an early adverse environment alters food preferences in adult life. We investigated whether IUGR is associated with spontaneous macronutrient preferences in humans. Two thousand sixty-three participants from a Brazilian birth cohort were evaluated at 24 y of age using a food frequency questionnaire, physical examination, anthropometric measurements, and biochemical assays (glucose, insulin, cholesterol, and tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
82
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 58 publications
16
82
0
3
Order By: Relevance
“…In support of this hypothesis, we found that young adult women who have experienced IUGR prefer carbohydrates over protein and have larger waist-to-hip ratios, despite having no signs of insulin resistance or diabetes mellitus (14). Other research groups report that there are specific food preferences among individuals exposed to nutritional shortage during gestation, manifesting as intake of high-fat diets (15) and higher energy intake (16) in late middle age.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…In support of this hypothesis, we found that young adult women who have experienced IUGR prefer carbohydrates over protein and have larger waist-to-hip ratios, despite having no signs of insulin resistance or diabetes mellitus (14). Other research groups report that there are specific food preferences among individuals exposed to nutritional shortage during gestation, manifesting as intake of high-fat diets (15) and higher energy intake (16) in late middle age.…”
supporting
confidence: 80%
“…Furthermore, in girls alone, eating impulse response scores at the age of 36 mo predicted both quantum of consumption of palatable fat and BMI values at the age of 48 mo, despite there being no such association with BMI at 36 mo. These data take on added significance in conjunction with the finding that young adult women with a history of IUGR show a preference for carbohydrates (14). …”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Wardle et al [47] observed that twin children from families with obese/overweight parents had modestly higher preferences for the taste of fatty foods, less liking for low-energy-dense foods, such as vegetables, and displayed stronger positive appetitive reactions to food and drink than children of lean parents. Other studies have reported that individuals with severe intrauterine growth restriction have altered nutritional intake later in life [48, 49]. Lussana et al [50] demonstrated that middle-aged adult participants exposed to famine in early gestation were twice as likely to consume a high-fat diet (> 39% energy from fat) than time controls, supporting long-term effects of intrauterine exposures.…”
Section: Formation and Development Of Eating Behavioursmentioning
confidence: 99%